Interaction of starch with some food macromolecules during the extrusion process and its effect on modulating physicochemical and digestible properties. A review - Ibrahim O. Mohamed (Carbohydrate Polymer Technologies and Applications, 2023)
Starch is one of the major macronutrients providing caloric value to the human diet, however, the rapid digestibility of starch is becoming a major concern for human health because it is associated with several chronic diseases. More focus has recently been placed on modifying starch digestibility by processing foods to contain higher levels of resistant starch, through physical modification of the molecular structure of starch, or the use of other non-starch ingredients like proteins, lipids, dietary fibers, and others to induce molecular interactions with starch and modify its physicochemical and digestibility properties. Extrusion technology is emerging as an efficient processing method that can simultaneously induce shearing, heating, and pressure in a precisely controlled manner capable of altering starch molecular structure and enhancing interactions with other non-starch molecules. This review will focus on the effects of extrusion processing parameters on starch molecular structure, interactions with other dietary macromolecules, and conformational changes that affect physicochemical and digestibility properties. The review will give a systematic hypothesis about how the ternary complexes (starch-protein-lipid) are formed during extrusion in an effort to improve the fundamental understanding required for subsequent research because information about the ternary complexes is scarce.